The Sisters of Our Lady of the Missions : from ultramontane origins to a new cosmology - Bruno-Jofré, Rosa del Carmen, 1946- (University of Toronto Press, 2020)
"This book guides the reader through the journey taken by the Canadian Province of Our Lady of the Missions (RNDM), from their establishment in Manitoba, Canada, in 1898, until 2008, when the congregation as a whole redefined its mission and vision. This vision was placed within the framework of eco-spirituality and inserted in a new cosmology that included the celebration of womanness and social justice. Using archival research, conducted in Winnipeg, Manitoba, Sturry, England, and Rome as well as oral interviews with RNDM sisters, this book deals with questions regarding the work of sisters in schools and the part they played in the educational state in formation. The details of the congregation's work in schools show how the sisters' educational work was related to the social characteristics of the communities (e.g., those of French Canadian settlers, British immigrants, the Métis population, and continental European immigrants), first in Manitoba and Saskatchewan, and later on in Ontario and Quebec. Rosa Bruno-Jofré argues that the congregation's work was part of a major attempt on the part of the Church to carve a space for itself in the educational state in formation. The Sisters of Our Lady of the Missions examines the impact of Vatican II in the 1960s, and into the 2000s, as well as the dismantling of neo-scholasticism, and the process of secularization of consciousness in society at large. The emerging issues led the congregation and the province to examine their individual and collective identity at the intersection of feminist theology, eco-spirituality, and a critique of western cosmology."--